2002
DOI: 10.1002/humu.9052
|View full text |Cite
|
Sign up to set email alerts
|

Identification of seven novel mutations of F8C by DHPLC

Abstract: Hemophilia A is an X-linked recessive disorder resulting from deficiency of Factor VIII (F8C), an important protein in blood coagulation. A large number of disease producing mutations have been reported in the F8C gene. However, a comprehensive analysis of mutations is difficult to conduct due to the large gene size, its many scattered exons, and the high frequency of de novo mutations. In this study, we performed analysis using PCR, Conformation Sensitive Gel Electrophoresis (CSGE), Denaturing High Performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…This phenomenon was also observed by others [7,8]. The observed frequency of S1269S polymorphism in the Turkish population was higher than previously reported frequency in Europe (6%) and China (18%) [9]. In addition, the observed 38% heterozygosity of the S1269S polymorphism, qualified it as an informative intragenic marker for F8 linkage analysis in the population.…”
Section: Introductionsupporting
confidence: 83%
“…This phenomenon was also observed by others [7,8]. The observed frequency of S1269S polymorphism in the Turkish population was higher than previously reported frequency in Europe (6%) and China (18%) [9]. In addition, the observed 38% heterozygosity of the S1269S polymorphism, qualified it as an informative intragenic marker for F8 linkage analysis in the population.…”
Section: Introductionsupporting
confidence: 83%
“…Interestingly, polyA tract insertions do not always cause severe HA. Indeed the c.3864_3870insA mutation identified here has been reported twice before and in one case causes only a mild phenotype [17,18]. It has been proposed that the reason some individuals with polyA tract insertions escape severe HA is that just as polyA stretches are regions of frequent errors in DNA replication they are also likely sites for errors in transcription, which may restore the reading frame and allow traces of a functional protein to be produced [19,20], as was observed in this case.…”
Section: Discussionsupporting
confidence: 58%
“…Forthis reason, we have decided to directlysequence factor VIII and factor IX genes,although DGGE waspreviously used in the laboratory (16). DHPLC technology could represent an intermediate choice, as recentlys hown by different groups (17)(18)(19),with lowrunning costs and excellent sensitivity compared with direct sequencing. In this study,9 6d ifferent mutations were identified.…”
Section: Discussionmentioning
confidence: 99%